Film Marketing Technique in Bangladesh-is YouTube Trailer the Most Effective Tool? (Global Journal of Human-Social Science, 2019)
In recent times, the film industry is becoming precisely phenomenon worldwide. But formerly gathering knowledge about this specific issue, film marketing theory,strategy, policy, and hierarchical procedure should maintain while practising. The research undertakes the historical analysis of films from the very past, several marketing policies and practice of Bangla movies and tries to identify their strategy of marketing. The questionnaire includes in-depth interviews of the audiences, and the sampling procedure is purposive sampling. The samples collected throughout the study explores the ethical issues of the essential film marketing techniques. Drawing on, the uses and Gratifications model of Active Audience Theory, this study discovers the methods and conclude that YouTube Trailer is the most compelling film marketing technique. Therefore, identification of the marketing strategy is supportive of the film to be blockbuster or successful in the theatre, and marketing of a movie generates countless impact to be widespread in the audience.
Keywords: the film industry; film marketing; film marketing techniques; active audience; youtube trailer